ANALISIS PERAN PEMBELAJARAN SENI RUPA DALAM MENGEMBANGKAN KREATIVITAS SISWA SEKOLAH DASAR - Rukoyah, Siti; Nursobah, Asep; Jaelani, Ihrom (Jurnal Intisabi, 2025)
Students’ creativity is the ability to generate original and meaningful works of art. This study aims to know the role of fine arts learning in developing the creativity of 4th grade students at SDN 1 Langkapsari, and to know the diffulties and solutions to the role of fine arts learning in developing students’ creativity at SDN 1 Langkapsari. This study employs a qualitative method under a phenomenological approach. The findings showed that visual art learning using a practice-based approach and freedom of expression is effective to foster students’ enthusiasm, imagination, and confidence in creating artwork. Although there were some difficulties such as lack of experience, limited imagination, and low of self-confidence, those difficulties were successfully overcome through a free thematic strategy based on students’ personal experiences. In addition, the teacher’s role as a facilitator was the key to develop students’ creativity and courage.